Adaptive event-triggered H∞ fuzzy filter design for nonlinear networked systems via asymmetric LKF approach. Issue 12 (August 2022) - Ma, Zhiyuan; Sheng, Zhaoliang; Lin, Chong; Chen, Bing
Abstract: This paper studies the problem of the fuzzy H ∞ filter design for nonlinear networked control systems through event-triggered communication (ETC) scheme. Firstly, an improved adaptive ETC scheme is proposed to save communication resources. Secondly, an asymmetric Lyapunov-Krasovskii functional (LKF) method is introduced in the H ∞ performance analysis of filter error systems. Then, a new sufficient condition is obtained to meet the H ∞ performance by combining the method with membership-function-dependent approach. Further, a relaxed co-design method of the corresponding filter and event-triggering parameters is obtained. Finally, two numerical examples are provided to verify the advantage of the new approaches.